Pengaruh Keputusan Investasi, Kebijakan Hutang, dan Profitabilitas terhadap Nilai Perusahaan Sektor Food and Beverages yang Terdaftar di BEI Periode 2019-2021 - Vika Ayu Oktavia Sari; Deny Yudiantoro (Transformasi Manageria: Journal of Islamic Education Management, 2023)
This study aims to analyze the effect of investment decisions, debt policy and profitability partially and simultaneously on the value of companies in the Food and Beverages sector listed on the IDX for the 2019-2021 period. This research uses a quantitative approach with sampling technique using purposive sampling method, in order to obtain 25 companies from 72 companies. The data analysis technique used in this research is panel data regression analysis at a significance level of 5%. The program used in analyzing the data uses Eviews 9.0. The results of this study indicate that partially investment decisions and profitability have a significant effect on firm value while debt policy has no significant effect on firm value. The results of this research simultaneously show that investment decisions, debt policies and profitability have a significant effect on firm value. Keywords: Investment Decision, Debt Policy, Profitability, Firm Value